2019
DOI: 10.2169/internalmedicine.0597-17
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Meningitis Caused by β-lactamase Non-producing Ampicillin-resistant <i>Haemophilus influenzae</i> Type f in an Immunocompetent Woman

Abstract: We report the case of a 36-year-old previously healthy woman who presented with fever and headache. Blood and cerebrospinal cultures and a bacterial analysis revealed the presence of β-lactamase non-producing ampicillin-resistant Haemophilus influenzae type f (Hif) with sequence type 124. Accordingly, the patient was diagnosed with bacterial meningitis with bacteremia caused by Hif. She had normal humoral immunity, and antibiotic therapy rapidly improved her condition. Our case indicates that serotype replacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, in Japanese surveillance and case reports, the majority of invasive Hif strains have been susceptible to ampicillin; therefore, drug resistance has not been an issue 3 . However, in 2019, a series of outbreaks of meningitis in immunocompromised adults and bacteremia in children due to BLNAR Hif were reported 4,5 . Since the present case occurred in 2020, BLNAR may spread among invasive Hif infections as well as Hib.…”
Section: Antimicrobial Agent Mic (μG/ml) Interpretation Interpretive ...mentioning
confidence: 79%
See 1 more Smart Citation
“…However, in Japanese surveillance and case reports, the majority of invasive Hif strains have been susceptible to ampicillin; therefore, drug resistance has not been an issue 3 . However, in 2019, a series of outbreaks of meningitis in immunocompromised adults and bacteremia in children due to BLNAR Hif were reported 4,5 . Since the present case occurred in 2020, BLNAR may spread among invasive Hif infections as well as Hib.…”
Section: Antimicrobial Agent Mic (μG/ml) Interpretation Interpretive ...mentioning
confidence: 79%
“…3 However, in 2019, a series of outbreaks of meningitis in immunocompromised adults and bacteremia in children due to BLNAR Hif were reported. 4,5 Since the present case occurred in 2020, BLNAR may spread among…”
mentioning
confidence: 82%
“…Interestingly, Hif appears to show preference for the adult population, especially those with underlying/predisposing conditions, such as tobacco use, chronic obstructive pulmonary disease (COPD), alcohol abuse, diabetes mellitus, malignancy, and others [10] . Hif also has the ability to cause invasive disease in healthy adults with case reports of meningitis, septic arthritis, osteoarthritis and osteomyelitis, cellulitis, pneumonia with bacteremia or pleurisy, and supraglottitis/epiglottitis (supplementary Table 1) [27,[37][38][39][40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that comorbid diseases, such as chronic obstructive pulmonary disease, malignancy, and immunosuppression, are risk factors for invasive infections caused by H. influenzae (3). To compare this case with the trend in recent invasive Hif infections, the authors surveyed case reports on PubMed using the search terms "H. influenzae type f" and "adult" and used the results to build a summary table (Table 4) of case report of invasive Hif infections since 2013, when routine immunization against Hib started in Japan (18)(19)(20)(21)(22)(23)(24). In these cases, the median age was 63 years old, with some differences in sex.…”
Section: Discussionmentioning
confidence: 99%